Simulation of highly elastic fluid flows without additional numerical diffusitivity - Basombrío, Fernando Guillermo; Buscaglia, Gustavo C.; Dari, Enzo A. (Comisión Nacional de Energía Atómica; Argentina, 1990)
Fil: Basombrío, Fernando Guillermo Comisión Nacional de Energía Atómica; Argentina